Benzo[a]phenoxazines as Potential Anti-Inflammatory Drugs - Joana Pinto; M. Sameiro T. Gonçalves; David M. Pereira (Chemistry Proceedings)
The chemical diversity of natural products provides a promising source of anti-inflammatory drugs, notably targeting COX-2, whose activity is associated with inflammatory processes and carcinogenesis. The COX-2 and LOX inhibitory capacity of several benzo[a]phenoxazines, N- and O-heterocyclic compounds, was studied. The kinetic assay results revealed that these molecules significantly inhibit COX-2 activity, highlighting their promise as potent anti-inflammatory agents.